Tekanan Waktu Memoderasi Pengaruh Independensi Auditor dan Komitmen Organisasi pada Kinerja Auditor KAP di Provinsi Bali - Arta Pratiwi, Made Cintia; Bagus Dwirandra, A.A. Ngurah (E-Jurnal Akuntansi; Vol 23 No 2 (2018)DO - 10.24843/EJA.2018.v23.i02.p09, 2018)
This study aims to test the ability of time pressure to moderate the influence of auditor independence and organizational commitment to the performance of auditors at Public Accounting Firm in Bali Province registered with Indonesian Institute of Certified Public in 2017. The sample of this research is 76 auditor by using saturated sampling technique as sample determination method . Data collection method is questionnaire. Moderated Regression Analysis (MRA) is used as a data analysis technique in this study. The results of this test indicate that auditor independence has negative effect on auditor performance, organizational commitment and time pressure have positive effect on auditor performance and time pressure unable to moderate influence of auditor independence to auditor performance and time pressure unable to moderate influence of organizational commitment to auditor performance